IMPROVING NINTH GRADE STUDENTS’ SPEAKING SKILL THROUGH THE APPLICATION OF PROBLEM BASED LEARNING (PBL) METHOD AT SMPN 3 TUNGKAL JAYA MUBA - Padmasari Agustise (Universitas PGRI Palembang, 2022)
This research is aimed at improving the ninth-grade students’ speaking skill through Problem Based Learning (PBL) method when it is applied in teaching speaking. The research was carried out through action research. The researcher acted with the students and the English teacher as the collaborator. The subjects of the research were 20 students of Ninth Grade of SMPN 3 Tungkal Jaya, Musi Banyuasin in the academic year of 2021/2022. The data collection included the application of Problem Based Learning method in three cycles. The data were analyzed using quantitative and qualitative data. The research findings showed that Problem Based Learning method improve students’ speaking skill. It enables students to practice some speaking techniques in the form of group work, and it eases them in improving speaking. The improvement of speaking skill can be seen from the result of speaking test which has the mean score test 1 is 50%, test 2 is 70% and test 3 is 85%. This research also showed that the activities in Problem Based Learning enhance students’ skill in improving speaking skill. The conclusion suggests that the application of Problem Based Learning method improve the ninth grade students’ speaking skill effectively at SMPN 3 Tungkal Jaya, Musi Banyuasin.